2014
DOI: 10.1080/09658416.2013.863899
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of explicit form-focused instruction on morphosyntactic development

Abstract: This study explores whether and to what degree explicit form-focused instruction (FFI) facilitates the use of morphosyntactic forms in second language oral production and also whether it has differential effects on morphosyntactic forms with different linguistic variables. Twenty-seven university-level Chinese EFL participants were randomly assigned to a control group and an experimental group. While the control group watched a television episode in English, the experimental group completed two form-focused ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
(50 reference statements)
1
6
0
1
Order By: Relevance
“…This finding confirms a conclusion by N. Ellis () that salience is a key element that triggers selective attention in L2 learning. In addition, it supports a broader view that learners demonstrate varied manifestations of metalinguistic knowledge of structures that vary in terms of their inherent linguistic characteristics (Xu & Lyster, ).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This finding confirms a conclusion by N. Ellis () that salience is a key element that triggers selective attention in L2 learning. In addition, it supports a broader view that learners demonstrate varied manifestations of metalinguistic knowledge of structures that vary in terms of their inherent linguistic characteristics (Xu & Lyster, ).…”
Section: Discussionsupporting
confidence: 70%
“…Although it has been broadly held that FFI helps students develop metalinguistic knowledge of grammar rules (Norris & Ortega, ; Spada, ; Spada & Tomita, ), studies have reported mixed effects on grammatical forms with variable inherent linguistic characteristics. Xu and Lyster () studied the differential effects of FFI on the development of metalinguistic knowledge of three morphosyntactic forms (noun plural, regular and irregular past tense, and third‐person singular) in oral production by Chinese‐speaking learners of English. These three structures show variable complexity and regularity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dado que las diferencias con el otro grupo fueron estadísticamente signifi cativas, es posible afi rmar que estas tareas son decisivas en los resultados. Este hallazgo 33.2 2017 confi rma estudios anteriores que señalan que los aprendientes pueden benefi ciarse de la refl exión enfocada en la lengua (Ellis 2002;Lyster 2004) y que las explicaciones gramaticales explícitas presentan ventajas para los aprendientes (Alanen 1995;De Graaf 1997;Rosa y Leow 2004;Xu y Lyster 2014).…”
Section: Discussionunclassified
“…Another factor to consider is the importance of linguistic salience in the development of L2 knowledge of grammatical properties/features (Azaz, 2017; Azaz & Frank, 2017; Nassif, 2019; Xu & Lyster, 2014). As Azaz (2017) stated, in the course of the acquisition of salient features which are easy to notice in the input, metalinguistic knowledge plays an important role, suggesting the relevance of explicit instruction in the development of the features which are of low salience.…”
Section: Introductionmentioning
confidence: 99%